First-Line Irinotecan Combined with 5-Fluorouracil and Leucovorin for High-Grade Metastatic Gastrointestinal Neuroendocrine Carcinoma. Issue 1 (January 2013) - Du, Zedong; Wang, Yi; Zhou, Yi; Wen, Feng; Li, Qiu
Aim and background: High-grade gastrointestinal neuroendocrine neoplasms, ie, poorly differentiated neuroendocrine carcinomas, with no effective therapeutic approaches, have a high ability to metastasize. Methods: A review of the hospital information system was performed. Patients with histologically proven gastrointestinal neuroendocrine carcinoma who were treated with irinotecan combined with 5-fluorouracil and leucovorin in a first-line setting were eligible for analysis. We extracted information on age, sex, disease stage, laboratory findings, radiological findings, pathological findings, chemotherapy, effectiveness and adverse events of therapy, and outcomes. Results: Eleven patients were included in the study. Partial response was observed in 7 patients. Median progression-free survival and overall survival were 6.5 (95% CI, 5.1–7.9) and 13.0 (95% CI, 9.8–16.2) months, respectively. No treatment-related deaths occurred. Conclusions: The results demonstrated that irinotecan combined with 5-fluorouracil and leucovorin is an active regimen with acceptable toxicity for patients with metastatic high-grade gastointestinal neuroendocrine carcinoma that merits further investigation in prospective trials.